Prevalence, characteristics, and diabetes management in children with comorbid autism spectrum disorder and type 1 diabetes. Issue 5 (8th May 2019) - Stanek, Kelly R.; Youngkin, Erin M.; Pyle, Laura L.; Raymond, Jennifer K.; Driscoll, Kimberly A.; Majidi, Shideh
Abstract : Objective: To determine autism spectrum disorder (ASD) prevalence within our pediatric type 1 diabetes (T1D) clinic population and determine clinical characteristics and technology used by individuals with both ASD and T1D compared to matched controls with T1D alone and compared to our overall pediatric T1D clinic. Methods: Medical chart review showed 30 individuals with both ASD and type 1 diabetes (ASD + T1D). Controls (n = 90) were matched for age, sex, race/ethnicity, and T1D duration. ASD + T1D was compared to both matched controls and the pediatric T1D clinical population. Results: ASD prevalence in the pediatric T1D population was 1.16% (CI 0.96‐1.26). Compared to the T1D clinic, ASD + T1D had more males (93% vs 52%; P < 0.0001), lower hemoglobin A1c (HbA1c) (8.2% vs 8.9%; 66 vs 74 mmol/mol; P = 0.006), and lower insulin pump (CSII) use (37% vs 56%; P < 0.0001). No differences were found between ASD + T1D and matched controls in HbA1c or blood glucose checks per day. The ASD + T1D group was less likely to use CSII than matched controls (37% vs 61%; P = 0.03). HbA1c did not change after CSII initiation in ASD + T1D, but increased for matched controls. Conclusions: Prevalence of ASD in the pediatric T1D population is comparable to the general population in Colorado. Individuals with ASD may experience barriers limiting CSII use, but achieve equivalent glycemic control compared to those without ASD. CSII may be more effective in maintaining lower HbA1c over time in those with ASD than in those without ASD.